EFFECTS OF THE RADIAL EXTRACORPOREAL SHOCK WAVE THERAPY (rESWT) IN PATIENTS WITH CALCIFIC TENDINOPATHY OF SHOULDER - Dragicevic-Cvjetkovic, Dragana M; Erceg-Rukavina, Tatjana O; Manojlović, Slavko Lj (Scripta Medica, 2019)
Introduction: Calcific tendinopathy (CT) of shoulder is frequently a painful condition that is considered when there are calcium deposits in the tendons of the rotary cuff. There are many options for treatment starting with therapeutic options like medicaments, physical therapy and radial extracorporeal shock wave therapy (rESWT). If conservative treatment fails, then next option is surgical treatment. The purpose of this study was to investigate the outcome effect of rESWT in patients with calcific tendinopathy. Material and Methods: A prospective study from February 2010 to March 2019 monitored 67 patients with CT of the shoulders of the average age of 47.06 ± 15.2 who were treated with a rESWT. All patients were evaluated clinically with selected radiographic shoulder before therapeutic intervention. The treatment protocol consisted of a sound pressure intensity of  3 bar, a wave frequency of 14 / sec, a total of 2,000 waves per session. All patients performed a treatment consisting of the three sessions described each seven days. The outcome parameters were VAS scale of pain and shoulder radiography before and after therapy. The Student's t-test was used in the statistical analysis. Results: A clinical and radiographic improvement was recorded in 70% of patients in the treatment of CT of the shoulder 6 weeks after the therapy was performed with a rESWT (p